2017
DOI: 10.1590/1518-8345.1871.2932
|View full text |Cite
|
Sign up to set email alerts
|

Elder abuse within the family environment in the Azores Islands

Abstract: Objectives:to dimension abuse against vulnerable adults within the family and community environment in the Azores Islands, identify risk factors for abuse and describe the profile of an abused elder. Method:descriptive cross-sectional study. Random sampling. The instruments used were: clinical histories of the users, Mini-Mental State Examination, Index of Independence in Basic Activities of Daily Living, Family APGAR Scale, Elder Abuse Suspicion Index and Social Work Assessment Form. Descriptive statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
0
3
0
14
Order By: Relevance
“…Posteriormente, realizou-se a seleção mediante leitura na íntegra dos artigos considerados potencialmente elegíveis, cujos títulos e resumos informavam evidências sobre a violência contra pessoas idosas, totalizando 17 artigos. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) Todos os artigos da base CINAHL encontravam-se em duplicidade com outras bases de dados e, por isso, foram excluídos (Figura 1).…”
Section: Resultsunclassified
“…Posteriormente, realizou-se a seleção mediante leitura na íntegra dos artigos considerados potencialmente elegíveis, cujos títulos e resumos informavam evidências sobre a violência contra pessoas idosas, totalizando 17 artigos. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) Todos os artigos da base CINAHL encontravam-se em duplicidade com outras bases de dados e, por isso, foram excluídos (Figura 1).…”
Section: Resultsunclassified
“…Over the years, women have become more independent in society; however, a sexist culture still prevails, so that women are commonly associated with fragility and treated without respect, being often deprived of their ability to control and manage resources, which is especially difficult for older women [21,2324]. Regarding civil status, an adverse situation was found in this study: widowed, separated, divorced and single older individuals were found to be at greater risk of maltreatment, probably because marriage, over the years, exerts a protective effect in situations of conjugal conflict [8,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…Acil servisler, yaşlı istismarına bağlı sebeplerle önemli bir başvuru yeri olduğundan bu derlemenin amacı, yaşlı istismar konusunu ele almak ve acil servis ortamında yaşlı istismarını anlama, tanıma, tarama ve bakım ile ilgili konulara dikkati çekmektir. Anahtar sözcükler: Acil servis, Yaşlı, İstismar gerekse sağlık çalışanların bilgisizliği ve endişeleri nedeniyle çok fazla dile getirilmeyen, çoğunlukla gizli kalan ve bu nedenle tam görülme oranları bilinmeyen bir sağlık sorunudur (3,(7)(8)(9)(10). Mevcut kanıtlara dayanarak, DSÖ (Dünya Sağlık Örgütü) 2019 yılında 60 yaş ve üstü kişilerin %15.7'sinin istismara maruz kaldığını tahmin etmektedir (7) 2015 yılında dünya genelinde 6 yaşlıdan 1'inin istismara uğradığı görülmüştür (11).…”
Section: öZunclassified
“…Yaşlı istismarı, Yaşlı İstismarı Önleme Bildirgesi'nde "temel ihtiyaçlarını karşılamada yetersiz ve savunmasız olan yaşlı bir insan için zarar ya da sıkıntıya neden olan bir güven beklentisinin olduğu herhangi bir ilişkide meydana gelen tek bir ya da tekrarlanan eylem ya da uygun eylem eksikliği" olarak tanımlanmıştır (3,(7)(8)(9). Ulusal Yaşlı Kötüye Kullanım Merkezi, Ulusal Yaşlı Kötüye Kullanım Merkezi, yaşlı istismarı ve ihmalini Tablo 1'de görüldüğü gibi sekiz boyutta ele almıştır.…”
Section: Tanımıunclassified